2012
DOI: 10.1063/1.3676720
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure study of tetramethylsilane by Raman spectroscopy

Abstract: High-pressure behavior of tetramethylsilane, one of the Group IVa hydrides, was investigated by Raman scattering measurements at pressures up to 142 GPa and room temperature. Our results revealed the phase transitions at 0.6, 9, and 16 GPa from both the mode frequency shifts with pressure and the changes of the full width half maxima of these modes. These transitions were suggested to result from the changes in the inter- and intra-molecular bonding of this material. We also observed two other possible phase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
21
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 35 publications
(36 reference statements)
5
21
1
Order By: Relevance
“…For the Phase I of DMSe below 4.4 GPa, all the modes exhibit the blue‐shift with increasing pressure, and it is not found that some vibrational modes (such as ν 4 and ν 5 ) relative to the CH 3 group show a negative pressure coefficients as listed in Table although it is uncertain for Mode ν 4 to undergo such behavior due to the influence by the strong peak of diamond at 1,332 cm −1 with increasing pressure. To the best of our knowledge, nearly all compounds including CH 3 group(s) were observed to have a negative pressure coefficients at low pressures such as CH 3 HgM (M = Cl, Br, and I), (CH 3 ) 2 XM (X = Sn and Tl), X(CH 3 ) 4 (X = Si, Ge, and Sn), and (CH 3 ) 2 S, which is regarded as a typical character of the rotational motions of the CH 3 group. Additionally, it is found that each mode has very different pressure coefficient as shown in Table , and C–H stretch modes exhibit the most intensive pressure effects in mixed phase; the next few modes are C–Se stretch, CH 3 deformation, and C–Se–C deformation sequentially, which is reasonable for the pressure‐induced vibrational affects in a molecule except for the CH 3 deformational modes .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…For the Phase I of DMSe below 4.4 GPa, all the modes exhibit the blue‐shift with increasing pressure, and it is not found that some vibrational modes (such as ν 4 and ν 5 ) relative to the CH 3 group show a negative pressure coefficients as listed in Table although it is uncertain for Mode ν 4 to undergo such behavior due to the influence by the strong peak of diamond at 1,332 cm −1 with increasing pressure. To the best of our knowledge, nearly all compounds including CH 3 group(s) were observed to have a negative pressure coefficients at low pressures such as CH 3 HgM (M = Cl, Br, and I), (CH 3 ) 2 XM (X = Sn and Tl), X(CH 3 ) 4 (X = Si, Ge, and Sn), and (CH 3 ) 2 S, which is regarded as a typical character of the rotational motions of the CH 3 group. Additionally, it is found that each mode has very different pressure coefficient as shown in Table , and C–H stretch modes exhibit the most intensive pressure effects in mixed phase; the next few modes are C–Se stretch, CH 3 deformation, and C–Se–C deformation sequentially, which is reasonable for the pressure‐induced vibrational affects in a molecule except for the CH 3 deformational modes .…”
Section: Resultsmentioning
confidence: 97%
“…It is a general rule that an increase in pressure should increase the A–H bond wavenumbers of weak and medium‐strength hydrogen bonds; however, the appearance of the softening behavior has been a characteristic in hydrogen‐rich compounds containing CH 3 or NH 3 groups where order–disorder transitions take place with temperature or pressure. For example, the pressure‐induced restricted rotation of NH 3 groups and the locked NH 3 positions in the compounds of dihydrogen bonding molecule of NH 3 BH 3 , CH 3 HgM (M = Cl, Br, and I), (CH 3 ) 2 XM (X = Sn or Tl), X(CH 3 ) 4 (X = Si, Ge, and Sn), and (CH 3 ) 2 S can be reflected by the softening of CH 3 vibrational mode in the Raman spectra. For the CH 3 HgM (M = Cl, Br, and I), this softening behavior existed with the pressure up to 0.59 GPa for CH 3 HgCl, 1.25 GPa for CH 3 HgBr, and 0.5 GPa for CH 3 HgI, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, very recently experiment shows the possible decomposition of SiH 4 under irradiation from X-ray and lasers. 46,47 Excitingly, Si(CH 3 ) 4 , one of the tetra-alkyl hydrides of group IVa element, was found to be stable up to 140 GPa in our recent work, 48 although it remains insulating. Above 96 GPa, the sudden disappearing of original vibrational modes and appearing of new Raman modes make the metallization of tetramethylsilane more complex.…”
Section: Introductionmentioning
confidence: 99%
“…This softening only exists in the liquid phase and the related modes disappear at around 5 GPa, which is different from the case of TMS under pressure. 48 The softening of CH 3 groups of TMS remains until 9 GPa and the related modes do not disappear in the whole pressure region of 30 GPa. In phase I, the mode ν ′ 6 of TMGe also undergoes blue-shift, but its dν/dP is larger than those of ν 6 and ν 7 modes, manifesting that new high-pressure structure is prone to be compressed.…”
mentioning
confidence: 99%